Design and Analysis of a Broadcast Network Using Logical Segmentation - Anyasi Francis; Uzairue Stanley; Enehizena O.N.; Victor Matthews Olu; Amaize Peter; Nsikan Nkordeh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This study shows how the network performance of a flat switch network in the main library complex of Ambrose Ali University (AAU), Ekpoma can greatly be improved by logical segmentation. A survey of the flat switch network of the library complex was carried out to ascertain the physical and logical topology of the network and the number of hosts and network devices available. The kind of traffic transmitted over the network was also considered. Riverbed Modeler Academic Edition was used to simulate two replicas of the library network. One of the simulated networks was logically segmented by implementing Virtual Local Area Network (VLAN). Statistics like traffic dropped, traffic forwarded, traffic received, broadcast traffic dropped and traffic sent in bits/sec or packets/sec were collected from both simulations and the results were analyzed and compared. The results from the simulations showed that the application of VLAN immensely enhanced the network performance by about 75%(depending on the size of the network) because the logical segmentation increased the number of broadcast domain while reducing each of the broadcast size. This further implied that poor network design and large broadcast domain in a network, gravely affect the performance of a network.